THE IMPACT OF THE UNCONDITIONAL CASH TRANSFER PROGRAM (BLT) ON CIGARETTE CONSUMPTION IN INDONESIAN SOCIETY - Inayati Nuraini Dwiputri (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
One of the purposes of the unconditional cash transfer program (Bantuan Langsung Tunai/BLT) was to help the poor and near-poor households to fulfill their basic needs. This study attempted to identify the impact of the BLT on cigarette consumption in society; as it is well known that smoking has more disadvantages than benefits. The study used data from the Indonesian Family Life Survey (IFLS) 2000 and 2007 to capture the impact of the BLT on the cigarette consumption of households. By controlling for the characteristics of the respondents, and using the fixed effect at household and village level as an estimation technique, the empirical results showed that in general there was a changing pattern of cigarette consumption in Indonesian society, to which the BLT program has contributed. By influencing the savings of households, the BLT program has significantly decreased cigarette consumption in Indonesia. It could be explained by the permanent income hypothesis, where the BLT transfer can be categorized as a transitory income in that hypothesis. This study can be an input and consideration for the transfer policy’s implementation in Indonesia in particular.